Evaluation of water productivity and irrigation performance in center pivot and rainfed systems using the WaPOR database - Valdemiro Simão João Pitoro; José Rafael Franco; Pedro Vitor Soares Adrien; Victor Crespo de Oliveira; Rodrigo Máximo Sánchez-Román (Modeling Earth Systems and Environment, 2026)
Remote sensing has become a strategic tool for monitoring irrigation systems, especially in regions with a lack of local agroclimatic and field-scale management data. This study evaluated the water productivity and irrigation performance of soybean cultivation in Pratânia, in the midwestern region of São Paulo State, Brazil, comparing a center pivot system (72.77 ha) and three rainfed areas (with an area of 53.74 ha) over three consecutive seasons (2022–2025). Local data, including crop yield, applied irrigation depth, and climatic variables, were compared with remote sensing products from the WaPOR v3.0 database (precipitation—P, reference—ET o and actual evapotranspiration and interception – AETI, and net primary production - NPP) Irrigation performance was assessed using equity (EqD), relative water deficit (RWD), and Water Productivity (WP) as a key performance indicator. Results showed that local yields in irrigated fields were 5.16, 4.63, and 4.12 t ha⁻¹ for the 2022–2023, 2023–2024, and 2024–2025 cropping seasons, respectively. In comparison, WaPOR-based estimates for the same periods were 7.15, 5.79, and 7.00 t ha⁻¹, indicating a consistent trend of yield overestimation by the platform, although it successfully captured seasonal variability. WUP ranged between 1.24 and 1.66 kg m⁻³ in irrigated cultivation, with similar values under rainfed conditions. RWD values (< 0.13) indicated low exposure to water stress in both systems. However, EqD indicator effectively distinguished the two management systems; irrigated fields maintained high uniformity (CV: 3.31–5.68%), whereas rainfed areas exhibited significantly higher spatial heterogeneity (CV: 8.13–10.36%) due to irregular precipitation distribution. This demonstrates the leverage of the WaPOR dataset in capturing field-scale water status. While absolute yields were overestimated compared to local data, the platform proved robust in identifying spatial performance gaps and monitoring irrigation impacts. Therefore, WaPOR is recommended as a reliable proxy for irrigation auditing and strategic decision-making in regions where in-situ monitoring is limited.

Hydrodynamic and water quality modelling of a free water surface constructed wetland for urban runoff mitigation - A. Martínez-Biosca; C. Hernández-Crespo; E. Asensi; I. Andrés-Doménech; M.Eugenia Rodrigo-Santamalia; V. Benedito-Durá; M. Martín (Ecological Modelling, 2026)

Peptide and osteological evidence for sex bias in megalithic tombs of La Lora region, Northern Iberia - Angélica Santa Cruz; Teresa Fernández-Crespo; Ana María Casas-Ferreira; Miguel del Nogal Sánchez; José Luis Pérez Pavón; Rodrigo Villalobos García; Miguel Moreno Gallo; Javier Basconcillos-Arce; Germán Delibes de Castro (Archaeological and Anthropological Sciences, 2026)
Burial patterns of ancient communities based on the analysis of human remains are difficult to define. In this regard, the existence of a sex bias in megalithic tombs of western Europe remains unclear. Sex estimation using standard osteological methodologies based on dimorphic features is a complex task in commingled and fragmentary human skeletal assemblages, as those found in megalithic burials usually are. Fortunately, advances in molecular archaeological research have made it possible to accurately estimate karyotypic sex. In this work, karyotypic sex is estimated from 85 individuals of all age groups from the megalithic burials of La Lora region (Burgos, Spain) through amelogenin peptides from dental enamel to compare with and extend osteological sex estimations and to calculate sex ratios in these assemblages. The results suggest an overall over-representation of males, in agreement with previous osteological data, despite inter-site variability. Some diachronic variations in the sex ratio have also been detected, which may nuance the trend. Specifically, an increase in the ratio of males at the end of the 4th millennium cal. BC, which may be linked to diachronic changes related to social organisation. The results also suggest that sex-related selective burial in non-adult groups would be less restrictive, as more juvenile females were identified, which could point towards patterns of adult female exogamy.

Response of future near-surface ozone extremes in Europe to changes in precursor emissions and climate - Rodrigo Crespo-Miguel; Carlos Ordóñez; Ricardo García-Herrera; Steven T. Turnock (Atmospheric Environment, 2026)

Insights into the 100 largest European surface ozone episodes during spring–summer 2003–2022 - Tahimy Fuentes-Alvarez; Carlos Ordóñez; Ricardo García-Herrera; David Barriopedro; Rodrigo Crespo-Miguel; Miguel M. Lima (Science of The Total Environment, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Translational insights into statin-induced myotoxicity: Differential impact of lipophilic and hydrophilic statins on iPSC-derived skeletal muscle cells from patients with familial hypercholesterolemia - Raul Hernandes Bortolin; Felipe de Souza Leite; Andre Ducati Luchessi; Joyce Esposito; Igor Neves Barbosa; Renata Caroline Costa de Freitas; Abhijeet Rajendra Sonawane; Sasha Anna Singh; Elena Aikawa; Kayque Alves Telles-Silva; Thiago Dominguez Crespo Hirata; Antonia Pereira Rosa Neta; et al. (Toxicology, 2025)

Bycatch in the balance: the trawl fisheries impact on South American sea lions in San Matias Gulf, with comments on other species - M. Alejandra Romero; Laura Flórez; Matías Ocampo Reinaldo; Rodrigo Machado; Marina Coller; Enrique A. Crespo (Marine Mammal Science, 2025)
Bycatch is recognized as the primary threat to the viability of marine mammal populations. Given that bycatch levels display strong variations in space and time, knowledge of individual fishery‐marine mammal interaction will likely achieve working solutions. Here, we quantify marine mammal bycatch in the trawl fishery of the San Matías Gulf, Argentina, for the first time using data from onboard observers and fishing effort records. We infer expected annual mortality, evaluate the probability of exceeding conservation thresholds, and explore the importance of relevant covariates to account for broadscale differences in bycatch rates. The South American sea lion ( Otaria byronia ) was the most incidentally caught species (46 individuals), while only one common dolphin ( Delphinus delphis ) was taken. Bycatch of sea lions was primarily associated with the catch of the target species, proximity to colonies, and the identity of the target species. The maximum estimated bycatch rate was 0.12 animals/haul and 0.08 animals/tonne of target species landed, with significantly higher bycatch rates observed in the hake fleet. For the whole period, the annual bycatch mortality were below the reference points. Our findings highlight potential hotspots of marine mammal bycatch and provide valuable insights for refining future mitigation measures and enhancing conservation efforts.

Integration of spectroscopic techniques and machine learning for optimizing Phaeodactylum tricornutum cell and fucoxanthin productivity - Pedro Reynolds-Brandão; Francisco Quintas-Nunes; Constança D.F. Bertrand; Rodrigo M. Martins; Maria T.B. Crespo; Cláudia F. Galinha; Francisco X. Nascimento (Bioresource Technology, 2025)

Large-scale ozone episodes in Europe: Decreasing sizes in the last decades but diverging changes in the future - Rodrigo Crespo-Miguel; Carlos Ordóñez; Ricardo García-Herrera; Jordan L. Schnell; Steven T. Turnock (Science of The Total Environment, 2024)

Virulence genotype and phenotype of two clinical isolates of Arcobacter butzleri obtained from patients with different pathologies - Itsaso Baztarrika; Adrián Salazar-Sánchez; Silvia Hernaez Crespo; José Israel López Mirones; Andrés Canut; Rodrigo Alonso; Ilargi Martínez-Ballesteros; Irati Martinez-Malaxetxebarria (Archives of Microbiology, 2023)
The surge in human arcobacteriosis has increased interest in determining the mechanisms involved in the pathogenesis of Arcobacter butzleri . Here, genomic analyses and in vitro Caco-2 infection, motility, urease and antimicrobial susceptibility testing (AST) assays were used to characterise the virulence and antimicrobial resistance (AMR) determinants of strains HC-1, isolated from a patient with travellers’ diarrhoea, and HC-2, isolated from another with pruritus. AMR determinants conferring resistance to tetracycline ( tetO , present in both genomes) and to ampicillin and amoxicillin–clavulanic acid ( bla3 , present in HC-2) were identified. The same determinants associated with flagellum, chemotaxis, adhesion and invasion were detected in both, but HC-1 lacked eight flagellar genes. The urease cluster was only present in HC-1. Motility and urease tests confirmed the genetic differences between strains, but no genetic marker related to the inability of HC-2 to adhere and invade was identified. This inability could be conditioning the patient’s pathology.

Lipidomic analysis identified potential predictive biomarkers of statin response in subjects with Familial hypercholesterolemia - Alvaro Cerda; Raul Hernandes Bortolin; Marcos Yukio Yoshinaga; Renata Caroline Costa de Freitas; Carolina Dagli-Hernandez; Jessica Bassani Borges; Victor Fernandes de Oliveira; Rodrigo Marques Gonçalves; Andre Arpad Faludi; Gisele Medeiros Bastos; Rosario Dominguez Crespo Hirata; Mario Hiroyuki Hirata (Chemistry and Physics of Lipids, 2023)

LDLR and PCSK9 3´UTR variants and their putative effects on microRNA molecular interactions in familial hypercholesterolemia: a computational approach - Renata Caroline Costa de Freitas; Raul Hernandes Bortolin; Jessica Bassani Borges; Victor Fernandes de Oliveira; Carolina Dagli-Hernandez; Elisangela da Silva Rodrigues Marçal; Gisele Medeiros Bastos; Rodrigo Marques Gonçalves; Andre Arpad Faludi; Vivian Nogueira Silbiger; André Ducati Luchessi; Rosario Dominguez Crespo Hirata; et al. (Molecular Biology Reports, 2023)

Multi-objective optimization of the solar orientation of two residential multifamily buildings in south Brazil - Letiane Benincá; Eva Crespo Sánchez; Ana Passuello; Rodrigo Karini Leitzke; Eduardo Grala da Cunha; José Maria González Barroso (Energy and Buildings, 2023)

Investing in nature-based solutions: Cost profiles of collective-action watershed investment programs - Shiteng Kang; Timm Kroeger; Daniel Shemie; Marta Echavarria; Tamara Montalvo; Leah L. Bremer; Genevieve Bennett; Samuel Roiphe Barreto; Henrique Bracale; Claudia Calero; Aldo Cardenas; Julián Cardona; et al. (Ecosystem Services, 2023)

ENSO coupling to the equatorial Atlantic: Analysis with an extended improved recharge oscillator model - Rodrigo Crespo-Miguel; Irene Polo; Carlos R. Mechoso; Belén Rodríguez-Fonseca; Francisco J. Cao-García (Frontiers in Marine Science, 2023)
Introduction Observational and modeling studies have examined the interactions between El Niño-Southern Oscillation (ENSO) and the equatorial Atlantic variability as incorporated into the classical charge-recharge oscillator model of ENSO. These studies included the role of the Atlantic in the predictability of ENSO but assumed stationarity in the relationships, i.e., that models’ coefficients do not change over time. A recent work by the authors has challenged the stationarity assumption in the ENSO framework but without considering the equatorial Atlantic influence on ENSO. Methods The present paper addresses the changing relationship between ENSO and the Atlantic El Niño using an extended version of the recharge oscillator model. The classical two-variable model of ENSO is extended by adding a linear coupling on the SST anomalies in the equatorial Atlantic. The model’s coefficients are computed for different periods. This calculation is done using two methods to fit the model to the data: (1) the traditional method (ReOsc), and (2) a novel method (ReOsc+) based on fitting the Fisher’s Z transform of the auto and cross-correlation functions. Results We show that, during the 20th century, the characteristic damping rate of the SST and thermocline depth anomalies in the Pacific have decreased in time by a factor of 2 and 3, respectively. Moreover, the damping time of the ENSO fluctuations has doubled from 10 to 20 months, and the oscillation period of ENSO has decreased from 60-70 months before the 1960s to 50 months afterward. These two changes have contributed to enhancing ENSO amplitude. The results also show that correlations between ENSO and the Atlantic SST strengthened after the 70s and the way in which the impact of the equatorial Atlantic is added to the internal ENSO variability. Conclusions The remote effects of the equatorial Atlantic on ENSO must be considered in studies of ENSO dynamics and predictability during specific time-periods. Our results provide further insight into the evolution of the ENSO dynamics and its coupling to the equatorial Atlantic, as well as an improved tool to study the coupling of climatic and ecological variables.

Contribution of green roofs to urban arthropod biodiversity in a Mediterranean climate: A case study in València, Spain - Vicent Benedito Durà; Enric Meseguer; Carmen Hernández Crespo; Miguel Martín Monerris; Ignacio Andrés Doménech; M. Eugenia Rodrigo Santamalia (Building and Environment, 2023)

Benthic Cyanobacterial Diversity and Antagonistic Interactions in Abrolhos Bank: Allelopathy, Susceptibility to Herbivory, and Toxicity - Felipe de Vargas Ribeiro; Taiara Aguiar Caires; Marcela Alvarenga de Almeida Simões; Paulo Iiboshi Hargreaves; Livia Bonetti Villela; Giovana de Oliveira Fistarol; Alexandre Brauns Cazelgrandi; Guilherme Henrique Pereira-Filho; Rodrigo Leão de Moura; Renato Crespo Pereira; Paulo Sergio Salomon (Frontiers in Marine Science, 2022)
Benthic cyanobacterial mats (BCMs) are conspicuous components of coral reef communities, where they play key ecological roles as primary producers among others. BCMs often bloom and might outcompete neighboring benthic organisms, including reef-building corals. We investigated the cyanobacterial species composition of three BCMs morphotypes from the marginal reef complex of Abrolhos Bank (Southeastern Brazil). Also, we assessed their allelopathic effects on coral zooxanthellae, their susceptibility to herbivory by fish, and their toxicity to brine shrimp nauplii. Morphology and 16S rDNA sequencing unveiled the cyanobacteria Moorena bouillonii , Okeania erythroflocculosa , Adonisia turfae , Leptolyngbya sp., and Halomicronema sp. as components of BCMs from Abrolhos. BCMs cell-free filtrates and extracts exerted an allelopathic effect by reducing the growth of the ex hospite Symbiodinium sp. in culture. BCMs-only treatments remained untouched in field susceptibility assays in contrast to macroalgae only and mixed BCMs-macroalgae treatments that had the macroalgae fully removed by reef fish. Crude aqueous extracts from BCMs were toxic to brine shrimps in acute assays. Besides unveiling the diversity of BCMs consortia in Abrolhos, our results cast some light on their allelopathy, antiherbivory, and toxicity properties. These antagonistic interactions might promote adverse cascading effects during benthic cyanobacteria blooms and in gradual shifts to BCMs-dominated states.

From Settlers to Subspecies: Genetic Differentiation in Commerson’s Dolphins Between South America and the Kerguelen Islands - Sebastián Kraft; MJosé Pérez-Alvarez; Carlos Olavarría; Rodrigo Moraga; C. Scott Baker; Debbie Steel; Paul Tixier; Christophe Guinet; Amelia Viricel; Paul Brickle; Marina Costa; Enrique Crespo; et al. (Frontiers in Marine Science, 2021)
Commerson’s dolphins ( Cephalorhynchus commersonii ) are separated into the subspecies C. c. commersonii , found along southern South America (SA) and the Falkland Islands/Islas Malvinas (FI/IM), and C. c. kerguelenensis , restricted to the subantarctic Kerguelen Islands (KI). Following the dispersal model proposed for the genus, the latter is thought to have originated from SA after a long-distance dispersal event. To evaluate this biogeographic scenario, a distribution-wide, balanced sampling of mitochondrial DNA (mtDNA) control region sequences was designed. New tissue samples from southern Chile, Argentina, FI/IM, and KI were added to published sequences from SA and KI, for a total of 256 samples. Genetic diversity indices, genetic and phylogeographic structure, and migration rates were calculated. One haplotype was shared between subspecies, with which all haplotypes of C. c. kerguelenensis formed a distinct group in the haplotype network. A new haplotype for C. c. kerguelenensis is reported. Differentiation in haplotype frequencies was found among localities within the distribution of C. c. commersonii , yet the phylogeographic signal was only statistically significant between subspecies. Coalescent-based historical gene flow estimations indicated migration between the northern and southern portions of the species’ range in SA as well as between SA and the FI/IM, but not between these and the KI. The net nucleotide divergence between dolphins from SA and the FI/IM was lower than the recommended threshold value suggested for delimiting subspecies, unlike that found between C. c. commersonii and C. c. kerguelenensis . The results are consistent with the model of post-glacial colonization of KI by South American C. commersonii , followed by an ongoing divergence process and subspecies status. Thus, C. c. kerguelenensis may represent the most recent diversification step of Cephalorhynchus , where isolation from their source population is driving a process of incipient speciation.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Genetic characterization of a putative new type of bovine papillomavirus in the Xipapillomavirus 1 species in a Brazilian dairy herd - Sarah Elizabeth Izzo Crespo; Michele Lunardi; Rodrigo Alejandro Arellano Otonel; Selwyn Arlington Headley; Alice Fernandes Alfieri; Amauri Alcindo Alfieri (Virus Genes, 2019)

The human dimension of the conflict between fishermen and South American sea lions in southern Brazil - Ana Carolina Pont; Silvio Marchini; Mônica Tais Engel; Rodrigo Machado; Paulo Henrique Ott; Enrique A. Crespo; Mariano Coscarella; Marina Schmidt Dalzochio; Larissa Rosa de Oliveira (Hydrobiologia, 2016)